(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2009)
The aim of the current study was to design a controlled porosity osmotic pump capsule of carvedilol .The capsule contains pore-forming water-soluble additives, which after coming in contact with water, dissolve, resulting in an in situ formation of a micro porous structure. The effect of different formulation variables, namely, ratio of drug to osmogent, solubilizing agent and level of pore former, different environmental media and stirring rate on the in vitro release was studied. Cellulose acetate (CA) was used as the semi permeable membrane. It was found that drug release rate increased with the increase in amount of osmogent and solubilizing and independent of different environmental media and stirring rate. Carvedilol release was, directly proportional to the level of pore former, glycerin, in the membrane. This system was found to deliver carvedilol at a zero-order rate.